Development and evaluation of a flipbook-based project-based learning e-module to enhance mathematical communication skills in digital mathematics education - Sutrisni Andayani; Dwi Rahmawati; Rahmad Bustanul Anwar (Journal of Advanced Sciences and Mathematics Education, 2026)
Background: The rapid advancement of digital technology in education requires students to develop not only problem-solving abilities but also effective mathematical communication skills. However, many students still experience difficulties in expressing mathematical ideas, reasoning, and solutions clearly. Consequently, innovative digital learning resources that integrate active learning approaches are needed to support meaningful mathematical communication. Aims: This study aimed to develop and evaluate a Flipbook-based Project-Based Learning (PjBL) e-module and determine its validity, practicality, and effectiveness in enhancing students’ mathematical communication skills. Method: This research employed a Research and Development (R&D) approach using the ADDIE model, consisting of Analysis, Design, Development, Implementation, and Evaluation stages. The e-module was developed by integrating Flipbook technology with PjBL activities. Data were collected through expert validation questionnaires, student response questionnaires, and classroom action research involving graduate students in Mathematics Education. Results: The findings indicated that the developed e-module achieved a validity score of 81%, categorized as highly valid. The practicality assessment yielded a score of 85.7%, indicating that the module was highly practical for learning activities. Furthermore, students’ mathematical communication skills improved from 74% in the first cycle to 82% in the second cycle, representing an 8% increase. Conclusion: The Flipbook-based PjBL e-module was found to be valid, practical, and effective in improving students’ mathematical communication skills and can serve as an innovative digital learning resource in mathematics education.